Tedizolid-Rifampicin Combination Prevents Rifampicin-Resistance on in vitro Model of Staphylococcus aureus Mature Biofilm - Gidari, Anna; Sabbatini, Samuele; Schiaroli, Elisabetta; Perito, Stefano; Francisci, Daniela; Baldelli, Franco; Monari, Claudia (Frontiers in Microbiology, 2020)
Staphylococcus aureus infections associated with implanted medical devices are difficult to treat and require long-lasting antibiotic therapies, especially when device removal is not possible or easy such as in the case of joint prostheses. Biofilm formation is a major cause of treatment failure and infection recurrence. This study aimed to test, for the first time, the in vitro combination of tedizolid plus rifampicin on methicillin-sensitive (MSSA ATCC 6538) and methicillin-resistant (MRSA ATCC 43300) S. aureus mature biofilm. Here, we demonstrated that the combination of tedizolid with rifampicin significantly disaggregated pre-formed biofilm of both strains, reduced their metabolic activity and exerted bactericidal activity at clinically meaningful concentrations. Notably, tedizolid was able to completely prevent the emergence of resistance to rifampicin. Moreover these effects were similar to those obtained with daptomycin plus rifampicin, a well-known and widely used combination. Preliminary results on some MRSA clinical isolates confirmed the efficacy of this combination in reducing biofilm biomass and preventing rifampicin resistance onset. Further in vivo studies are needed to confirm the validity of this promising therapeutic option that can be useful against biofilm-associated S. aureus infections.